Penerapan Problem Based Learning Tipe Snowball Throwing untuk Meningkatkan Hasil Belajar - Bariyah, Hudjatul; Wibowo, Kurniawan Budi; Khasanah, Uswatun (Jurnal Pendidikan Nusantara, 2022)
This study aims to determine students' ability level in Islamic Religious Education (PAI) through the snowball throwing method, which aims to improve learning outcomes at SMK Negeri 1 Trucuk Klaten. This type of research is called Classroom Action Research (CAR). The research design refers to the research design, which consists of two research cycles consisting of four stages, (1) planning, (2) action implementation, (3) observation, and (4) reflection. The research subjects of class X ATU 1 consisted of 35 students. Data collection techniques used teacher and student observation sheets, documentation and tests. Data analysis techniques using quantitative descriptive analysis. The results showed that the effectiveness of the application of the snowball throwing method could improve learning outcomes in the subject of Islamic Religious Education at SMK Negeri 1 Trucuk. This is based on the following: 1) the results obtained from learning outcomes have increased starting from pre-cycle observations, giving action using the snowball throwing method in the action in cycle I students get a complete score of 36.5%, and in the action in cycle II students get a complete score of 91 %, 2) the increase in learning outcomes affected the increase in class average, cycle I was 63.01 to 80.3 in cycle II, 3) there was activeness of students from cycle I including there were 15 active students in cycle I to 26 active students in cycle II. Based on these data, applying the snowball-throwing cooperative learning model can improve student learning outcomes in learning Islamic Religious Education.